Preembobracon gen. nov. (Hymenoptera: Braconidae: Doryctinae: Ypsistocerini: Embobraconina) from Brazil - Quicke, Donald L. J.; Butcher, Buntika A. (Zootaxa, 2015)
Preembobracon zaldivarriveroni gen et sp. nov. from Brazil is described and illustrated. It belongs to the poorly known tribe Ypsistocerini for which biology, is only partly known and then only for the genera of nominal subtribe which are both associated with termite colonies. Preembobracon displays both derived and plesiomorphic character states relative to Embobracon the only other genus of its tribe, and its position in relation to the other genera discussed. Its biology is unknown.